Here and There: Goals, Activities, and Predictions about Location from Geotagged Queries - West, Robert; White, Ryen W.; Horvitz, Eric (SGIR'13, 2013)
A signiﬁcant portion of Web search is performed in mobile settings. We explore the links between users’ queries on mobile devices and their locations and movement, with a focus on interpreting queries about addresses. We ﬁnd that users tend to have a primary location, likely corresponding to home or workplace, and that a user’s location relative to this primary location systematically inﬂuences the patterns of address searches. We apply our ﬁndings to construct a statistical model that can predict with high accuracy whether a user will be soon observed at an address that had been recently retrieved via search. Such an ability to predict that a user will transition to a location can be harnessed for multiple uses including provision of directions and trafﬁc information, the rendering of competitive advertising, and guiding the opportunistic completion of pending tasks that can be accomplished en route to a target location.